International Cooperation of the State Atomic Energy Corporation ROSATOM under Sanctions - Veronika I. Murina; Elena V. Zhiryaeva (RUDN Journal of Economics)
International cooperation is one of the most important and promising areas of activity of the state nuclear energy corporation ROSATOM (ROSATOM). The Corporation strives to become one of the international companies perceived as global technology leaders. Sanctions against the Russian economy are unprecedented. In the spring of 2023, sanctions were imposed by the United States against five organizations that are part of the ROSATOM. The purpose of the study is to assess the impact of sanctions on the international activities of the ROSATOM. The article provides a list of international markets where the ROSATOM operates in 2021-2022. The main competitors in the international markets of the Сorporation are identified: the natural uranium market, the uranium enrichment services market, the nuclear fuel fabrication market. An analysis of the position of the ROSATOM in selected segments of the global nuclear energy market in 2012-2022 was carried out. The main technical characteristics and sources of financing for the ROSATOM projects for the construction of nuclear power plants (NPPs) abroad are presented. The article uses materials from public annual reports of the ROSATOM for 2012-2022, as well as the Report on the State of the Global Nuclear Industry for 2022. Statistical methods were used to determine the share of the ROSATOM in segments of the global nuclear energy market; tabular and graphical methods were used to visualize the research results. In 2022, the ROSATOM was the leader in the world markets for uranium enrichment and conversion and had the largest portfolio of projects for the construction of nuclear power plants abroad. The main competitors of the ROSATOM in the international nuclear power plant construction market are China, France, South Korea, the USA and Japan. However, despite the successful activities of the ROSATOM, restrictions on access to Western technologies and finance create additional difficulties. In response to the imposed restrictions, the Corporation is actively developing domestic analogues and looking for ways to cooperate with countries that do not support sanctions.